ANALYTICAL FACTORS DEVELOPMENT OF ECOESTHETIC CULTURE OF FUTURE PRESCHOOL EDUCATION SPECIALISTS (Scientific journal of the Fergana State University, 2023)
The article discusses ecology, eco-aesthetics, eco-aesthetic education, the development and formation of ecological-aesthetic education in the education of preschool children, the preservation and protection of the natural resources gifted bu nature to future generations, and education in the spirit of love for nature, the laws issued by our government on ecological-aesthetic education on the basis of which there is talk about the tasks that are being done and should be done in the field of continuous education.